Evaluation of Homoeopathic Centesimal & Fifty-Millesimal Scale in the Management of Type 2 Diabetes Mellitus-A Comparative Study (Advancements in Homeopathic Research, 2024)
Background: Type-2 Diabetes Mellitus (T2DM)  is a chronic lifestyle disorder that calls for serious  concern in today's society due to its high morbidity  and mortality rates and long-term detrimental effects  on a number of body systems that can result in chronic  complications if left unchecked or uncontrolled. The  Homoeopathic system of medicine based on “Law of  Similia” has shown its efficacy in treatment of T2DM  as per various research studies. However, most of  the studies in the past were done on Centesimal  scale potency or mother tinctures, but there is lack  of study on effectiveness of Fifty millesimal scale  potency or comparative studies between both scales,  in cases of T2DM. This randomized parallel arms  study investigated the comparative effectiveness of  a homoeopathic medicine given in Centesimal scale  potencies versus Fifty millesimal scale potencies in  a sample (n= 60) of patients suffering from T2DM
Keywords: Centesimal scale potency; Fifty millesimal scale potency; Homoeopathy; RBS; SF 36; Type 2 diabetes mellitus (T2DM); Quality of life